The screening of breast cancer awareness and health behaviors of women age 40 to 69 in Mus, the least developed city in Turkiye: A population based, cross-sectional study. - ÖZAYDIN, AYŞE NİLÜFER (My University, 2015)
Background: Evaluation of the mammography-screening rate and breast cancer awareness of women aged 40-69 living in the city of Mus, the least developed city in Turkey. Methods: In this population-based cross-sectional study, 2420 women living in Mus and aged 40 to 69 were selected randomly from Turkish Statistical Institute's women list and surveyed. Results: In this study 2054 women were surveyed with a participation rate of 85%. The mammography-screening rate was 35%. 1% of the women had a diagnosis of breast cancer. Women aged from 50 to 59 had a higher rate of getting mammography in the last 2 years (42%). Also women having a regular OB-GYN visit, reading at least one newspaper a day and having social security insurance had a higher screening rate (42%, 44% and 39%, respectively). Women mostly declared TV and radio as the main sources of information on breast cancer (34%), but the women who were informed mainly by their doctors and nurses had a higher screening rate (42%). Women who knew breast cancer as the most common cancer in females (36%), who agreed that breast cancer is curable if detected early (36%) and who knew screening mammography is free of charge (42%) had a higher screening rate. Women who declared having a healthy diet (36%) and women who agreed to the phrase "I would get a mammography, if my doctor refers me to it" were more commonly screened (36%). The most common excuse for not having a mammography was "I didn't know it was necessary" (75%). 60% of women agreed that mammography exposes you to unnecessary radiation, and in this group the screening rate was significantly low (32%). Conclusions: We think that to increase participation to the breast cancer screening in low socioeconomic and low educational populations, accurate messages should be given especially on TV and radio. The messages should clearly highlight the survival benefits of being screened, the starting age for screening and mammography being free of cost. Also during all physician visits the women above 40 years of age should be referred to screening mammography programs.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE